Cambodia's Persistent Dollarization: Causes and Policy Options - Jayant Menon (Asian Development Bank (ADB), 2008)
Cambodia's economic and social achievements over the past ten years have been the most impressive in its history. Nevertheless, Cambodia today is still as dollarized, if not more so, than it was ten years ago. What is this so, and what, if anything, should the Government do? This paper attempts to answer both these questions, by examining the reasons behind the apparent paradox between a decade of economic and political improvements and continued dollarization, and drawing policy implications from it. We advise against pursuing enforced dedollarization, and advocate a policy option that focuses instead on accelerating accommodative reforms, especially in the financial sector and on legal and institutional reforms. We also identify a host of institutional barriers that need to be overcome to prepare the groundwork for a natural process of de-dollarization.
hdl:11540/1779
Keywords: E42; E58; F31; F33; 330; Cambodia; dollarization; exchange rates; currency board; hysteresis